Opposition Control of Turbulent Channel Flow with Upstream Sensors at Reτ=395 상류 센서를 이용한 Reτ=395의 난류 채널 유동 반대 제어 - Kim, Geumyoung; Yun, Jinhyeok; Lee, Jungil (Transactions of the Korean Society of Mechanical Engineers, B, 2023)
In this study, opposition control with upstream sensors is applied to the turbulent channel flow at Reτ =395. As a control input, the amplitude of the actuation at the wall is proportional to the transverse velocity at an upstream sensing location in the opposite direction and varies over time. We perform direct numerical simulations of turbulent channel flow and evaluate the control performance of skin friction reduction based on the locations of upstream sensor. It is shown that the opposition control with upstream sensors exhibits a better control performance than that with a sensor directly above the actuator. The use of upstream sensors for the opposition control effectively decreases the strength of streamwise vortices and velocity fluctuations near the wall, resulting in the maximum skin friction reduction of 26% for the turbulent channel flow with the optimal upstream sensor location.
Keywords: Active feedback control; Control inputs; Control performance; Direct-numerical-simulation; Opposition control; Skin friction reduction; Streamwise vortices; Transverse velocity; Turbulent channel flows; Upstream sensor; Active Feedback Control; Flow Control; Opposition Control; Turbulent Channel Flow; Upstream Sensor